Riview Of Celosia Flower Park : Tourist Perspective - Dyan Triana Putra; Nina Mistriani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
While the motivation for this study is the importance of the number of tourist visits to tourist attractions, tourism managers must understand and be able to explain well how they respond to consumer complaints based on the types of positive or negative tourist complaints on social media. The purpose of this study is to determine the strategic model to be used in developing artificial tourist attractions that have an important role in the tourism business. Intense business competition requires business people to be observant and astute in identifying existing opportunities and the behavior of their target market, the consumers. Since marketing managers, the spearhead of marketing in business, need to understand consumer behavior in purchasing decisions, which is key to increasing the success of marketing products, the study results suggest that a small review of consumer behavior in decision making, paying attention to and understanding consumer behavior on social media, is a good place to start. the importance of paying attention to, understanding, and providing a review of consumer behavior on social media in making decisions about purchase of services and products. This review will serve as a benchmark for tourism destination development strategies.